LEGAL PROTECTION OF CAPITAL MARKET INVESTORS IN THE EVENT OF A SUSPENSION OF STOCK TRADING ON THE INDONESIAN STOCK EXCHANGE BASED ON INDONESIAN LAW - Zakiar, Rafi Andriawan; Ikhwansyah, Isis; Faisal, Pupung (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Stock investment in the capital market is a high-risk high return investment. One of the risks faced by capital market investors is the stock trading suspension sanction imposed by the IDX as experienced by capital market investors in PT HK Metals Utama (HKMU) stocks. This suspension sanction is detrimental to investors due to the suspension of HKMU stock trading. Investors should be more careful to carry out risk management by cutting losses when they see a notation that HKMU shares will be suspended. This research aims to analyze the legal consequences and legal position of investors in the event of a suspension of stock trading and to analyze the legal actions or steps that can be taken by investors to sell their shares through off-exchange transactions.This research uses a research method with a normative juridical approach that is referred to the laws and regulations in the field of capital markets and applicable legal theories. The specification of this research is descriptive analytical. The data collection techniques used by researchers in this research are in the form of literature studies by searching for data as complete as possible from secondary data derived from primary and secondary legal materials that are relevant to related cases, then analyzed qualitatively. Based on the research results, the following can be obtained. First, the legal consequences experienced by investors are that investors cannot conduct buying and selling transactions of HKMU shares on the stock exchange as stated in Article I.5. IDX Regulation regarding Securities Suspension and investors have legal standing guaranteed by Articles 28-30 of the OJK Law and legal standing to conduct transactions outside the stock exchange as stipulated in Article 6 paragraph (3) POJK regarding Securities Transactions. Second, legal actions that can be taken by investors are selling their stocks through off-exchange transactions, submitting claims to OJK to make written orders by conducting disgrogement funds, and as a last resort can file a claim or lawsuit for compensation to the emiten.